2020
DOI: 10.1177/0194599819898861
|View full text |Cite
|
Sign up to set email alerts
|

Temporal Trajectory of Body Image Disturbance in Patients with Surgically Treated Head and Neck Cancer

Abstract: Objectives To characterize the temporal trajectory of body image disturbance (BID) in patients with surgically treated head and neck cancer (HNC). Study Design Prospective cohort study. Setting Academic medical center. Subjects and Methods: Patients with HNC who were undergoing surgery completed the Body Image Scale (BIS), a validated patient-reported outcome measure of BID, pretreatment and 1, 3, 6, 9, and 12 months posttreatment. Changes in BIS scores (ΔBIS) relative to pretreatment (primary endpoint) were a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
23
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 36 publications
3
23
2
Order By: Relevance
“…We similarly found that each individual ARPD question was predictive of impaired SF, demonstrating that aesthetic‐related distress is associated with social functioning. Up to 40% of HNC patients who undergo surgery may experience a protracted course of BID, lasting beyond 9 months postoperatively 15 . In this study, patients who were more than 1 year from reconstruction did not demonstrate any significant improvements in ARPD or SF scores.…”
Section: Discussionmentioning
confidence: 45%
“…We similarly found that each individual ARPD question was predictive of impaired SF, demonstrating that aesthetic‐related distress is associated with social functioning. Up to 40% of HNC patients who undergo surgery may experience a protracted course of BID, lasting beyond 9 months postoperatively 15 . In this study, patients who were more than 1 year from reconstruction did not demonstrate any significant improvements in ARPD or SF scores.…”
Section: Discussionmentioning
confidence: 45%
“…Our preliminary data, with high response rates and a large effect size suggest that psychosocial interventions (eg, CBT) to treat BID in HNC patients merit further study. A recent prospective cohort study aiming to characterize the natural history of BID demonstrated that HNC survivors with body image concerns (ie, a historical control for BRIGHT) show no improvement in BID (as measured by BIS scores) in the first 12‐months posttreatment 9 . The large effect size of BRIGHT on BID observed in this study thus appears to be substantial and differs from the temporal trajectory of untreated BID in the target population.…”
Section: Discussionmentioning
confidence: 53%
“…These changes occur in highly visible, socially significant parts of the body that are integral to self‐conception, communication, and interpersonal relationships 4‐6 . Based on single‐institution cross sectional and cohort studies of HNC patients, up to 75% express body image concerns when assessed using screening questionnaires or upon structured clinical interview 7‐9 . When severe, these image concerns can result in high rates of body image disturbance (BID), a disorder characterized by a displeasing self‐perceived change in appearance and/or function 4,10,11 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…With increased psychological distress, HNC patients have a four-time increased risk of death from suicide over the general population and two-time increased risk over non-HNC patients [ 155 , 156 ]. Patients who have undergone major reconstruction are susceptible to body image disorder, manifesting in dissatisfaction in appearance, lowered self-esteem, and tendency toward social isolation [ 148 , 157 , 158 ]. Active research in survivorship care aims to address these psychosocial effects.…”
Section: Emerging Developments: Cancer Survivorshipmentioning
confidence: 99%